Mainstreaming Biodiversity: Conservation for the Twenty-First Century - Redford, Kent H.; Huntley, Brian J.; Roe, Dilys; Hammond, Tom; Zimsky, Mark; Lovejoy, Thomas E.; da Fonseca, Gustavo A. B.; Rodriguez, Carlos M.; Cowling, Richard M. (Frontiers in Ecology and Evolution, 2015)
Insufficient focused attention has been paid by the conservation community to conservation of biodiversity outside of protected areas. Biodiversity mainstreaming addresses this gap in global conservation practice by “embedding biodiversity considerations into policies, strategies and practices of key public and private actors that impact or rely on biodiversity, so that it is conserved, and sustainably used, both locally and globally” (Huntley and Redford 2014). Biodiversity mainstreaming is designed to change those policies and practices that influence land uses outside of protected areas as well as to change economic and development decision-making by demonstrating the importance of conserving biodiversity for achieving development outcomes. The practice of mainstreaming is tied to implementation of the Convention on Biological Diversity and is practiced with billions of dollars of investment by development agencies, national government agencies, and the Global Environment Facility (GEF) and its implementing organizations as well as other donors. It is essential for the long-term survival of biodiversity inside and outside protected areas. However, it is virtually unheard of in the main conservation science field. This must change so as to bring careful documentation, analysis, monitoring, publishing and improvement of practices – all things that conservation science should provide as partners to practitioners of biodiversity mainstreaming. The situation is ripe for informed coordination and consolidation and creation of a science-driven field of biodiversity mainstreaming.